Empty forest syndrome: are we there yet? a preliminary analysis of the hunting and poaching activities in selected areas in Sabah, Malaysia - Saikim, Fiffy Hanisdah; Mohd. Yunus, Nurin Shahira; Mahyudin, Azniza; Nathan, Senthilvel K. S. S.; Muin, Hussien; Abdul Hamid, Arnie; Abdul Aziz, Nor Akmar; Mohd. Nordin, Nordiana; Salleh, Norhuda; Lo, Maximus Livon Ka Fu; George Kunai, Julia @. Ariana; Anak Jimbau, Petherine; et al. (Elsevier, 2023)
Hunting has long been known as a threat to the conservation of tropical wildlife (Peres, 2009), but in recent years it has become an increasingly urgent problem. In Borneo, Malaysia, for example, an estimated six million animals were hunted per year in the early 1990s, equivalent to about 36 animals per square kilometre (km2) of forest area (Bennett et al., 2000). The demand for game meat is driving consumption in the tropics far beyond sustainable levels. Thanks to improved transport and communication, markets can sometimes be hundreds of kilometres from the source. When animal populations are depleted in one place, hunters simply move on to another. Currently, public parks and other totally endangered zones cover about 18% of tropical rainforests. If we assume that natural resources in protected areas are successfully protected, we can be really sure that current conservation measures will help save most tropical biodiversity. Although protected area programmes in the forests have had some success in reducing environmental damage, they have been much less successful in preventing the extinction of the natural environment and the removal of its relatives. However, in most provinces in the tropics, poachers continue to access so-called protected areas with impunity. This study investigated the trend of wildlife hunting and poaching in some areas in Sabah. Interviews with local communities yielded information on hunting pressure on wildlife and the communities' dependence on wildlife resources. A total of 45 people was interviewed from six study areas: Sandakan, Tawau, Kota Belud, Tambunan, Keningau and Tenom. It was found that local communities hunt for food and that hunting is a common way of life for them. Based on the arrests of hunters by the Wildlife Rescue Units, a report on animal hunting was compiled by the Sabah Wildlife Department and analysed. The most commonly hunted animal is the bearded pig. Parts of bearded pigs were found in the cars of 76.97% of hunters arrested, followed by parts of sambar deer (13.7%). Throughout Sabah, the empty forest syndrome (EFS) is becoming a dangerous silent disaster. While most "simple" forest features are attractive to the eye, they are gradually losing their ecological function. Although this study is not exhaustive, the preliminary findings point to a serious EFS scenario in Sabah if everyone continues to neglect the syndrome and do nothing about it.